EXISTENTIAL CHOICE. AN ESSAY ABOUT THREE AFRICANS (REFLECTION ON AUGUSTINE’S CONFESSIONS) - S. V. Sannіkov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Via the life example of a great Christian hermit Augustine of Hippo and his «Confessions», the author of the essay considers the existential choice problem, which changes man’s course of life and displays its essence. Analyzing and deconstructing Augustine's self-reflection against the background of the texts by two other great Africans (A. Camou and J. Darrida), the article traces the foundations and main stages of the process of self-seeking in people who want to find themselves in a lost world. The purpose of the article is to analyze the intellectual, emotional and spiritual components of the process of taking epochal-making decisions versus the approaches of A. Camus and J. Derrida, prominent Augustine’s fellow countrymen, born in Algeria as well. Methodology. The research is based on the comparative historical analysis, allowing to identify and summarize some principles for the decision-making of the most important existential solutions. The use of comparative procedures made possible to show the ineffectiveness of self-contained Camus' and Darrida’s existential searches, and at the same time, demonstrate the success of finding selfhood and self-knowledge by Augustine, who was open for the gift descending from Above. The use of other general scientific methods, such as analysis, reduction, generalization, and retrospective method allowed the researcher to highlight some epistemological problems manifested in understanding and searching the Truth, as the most important and often unconscious human need. Augustine's openness to accepting Truth from Above and at the same time understanding the inability to seize it independently distinguishes him from similar searches of Jacques Darrida. Originality. The research has shown that the existential choice, which in contrast to ordinary choices, changes a man’s life and renders meaning to his existence, is made not with a volitional decision, but with a hardly explicable encounter connecting personal with over-personal being. Conclusions. The author concludes, that unlike the day-to-day choices-preferences, which can be made following a rational and ecstatic decision, the existential choice is a dialectic unity of Gift, coming from Above, and an intuitive unconscious faith of a person who accepts this Gift.